PERBANDINGAN DETERMINASI INKLUSI KEUANGAN DI INDONESIA DAN FILIPINA - Izzun Khoirun Nissa (Mutanaqishah : Journal of Islamic Banking, 2022)
In today's era, financial inclusion becomes an important thing for policy makers. They prioritize formulating a country's financial policies to build an inclusive financial system. The World Bank has recognized that financial inclusion covers 7 of the 17 sustainable development goals (Sustainable Development Goals). The method used in this research is panel data regression. By concluding that in terms of income, Indonesia and the Philippines show the same results where the three indicators of formal account, formal saving, and formal credit have a significant effect on income. This shows that the richer a person is, the higher the financial inclusion. Employment affects financial inclusion. Research in Indonesia and the Philippines shows the same results where work has an effect on formal accounts and formal savings. So it can be concluded that people who work have an effect on increasing financial inclusion compared to those who do not work.